Pemberian Insentif Terhadap Kepuasan Kerja Karyawan Satuan Non Vertikal Jaringan Pemanfaatan Air - Maria Kaok (Musamus Journal of Business & Management is a peer-reviewed journal published by Faculty of Ecconomics and Business, Musamus University, Merauke Papua Indonesia., 2020)
This study aims to analyze and measure the effect of providing incentives on employee job satisfaction, by taking the Implementation of certain Non-Vertical Work Units from the Papua Water Utilization Network in Papua - Merauke Province as the object of research. The population in this study amounted to 44 respondents and a sample of 44 respondents using nonprobability sampling or census sampling techniques. This research uses a quantitative approach with a simple regression analysis technique. Measurement of variables using a Likert scale and processed using SPSS version 22. The results of the calculation of the data using a simple regression analysis regarding the provision of incentives that affect employee job satisfaction Certain Non-Vertical Units Implementation of Papua Papua - Merauke Water Utilization Network, that the provision of incentives affects employee job satisfaction Specific Non Vertical Units Implementation of Papua Water Utilization Network Papua - Merauke Province, Judging from the results of the SPSS 22 output, the incentive variable (X) is obtained tcount = 4,589 while t-table = 1,682 and sig = 0,000 so Ha is accepted, because t-table <t-count. This means that the incentive independent variable (X) has a statistically positive and significant effect on the dependent variable of job satisfaction. Keywords: Incentives, Job Satisfaction